UJI EFEK ANTIHIPERGLIKEMIA INFUSA KANGKUNG DARAT (Ipomoea reptans Poir) PADA MENCIT SWISS JANTAN YANG DIINDUKSI STREPTOZOTOCIN - Helminawati Helminawati (Universitas Islam Indonesia, 2016)
The aim of this study is knowing the infusion effect of antihiperglicemia (Ipomoea reptan P.) to Swiss male mice which induced by streptozotocin (STZ) with blood glucose level and weight as measurement parameter. Swiss male mice's weight that used in this study are 20-30 gram. Thirty Swiss male mice divided into 6 groups (N=5) which is called as normal control group, positive control group will be given metformin 3,9mg/20gBW, negative control group will be given STZ during five days at dose 40mg/kgBW i.p and 3 treatment group will be given Ipomoea reptans infusion at dose 44,64mg/20gBW(P1), 89,28mg/20gBW (P2), 178,56mg/20gBW (P3) orally during 7 consecutive days from the 13th day to 19th day. Blood glucose levels and body weight Measurement will be done on day-0, day-13th, day-20th. The data taken has been analyzed by ANOVA and ANCOVA tests and the result has been compared between groups I, II, III and control group. Based on the data analyzed, there were no significant difference (p=0,05) between group I, II, III and control group. The result of this study showed that the average weight diabetic Swiss male mice compared with normal control weight increased 0.2grams/ day and the reduction in fasting blood glucose after being given Ipomoea reptans at dose 44,64mg/20gBB; 89.28 mg/20 gBB; mg/20gBB 178.56 consecutively 10.29%; 29.66%, -4.42%, 21.27%, 34.44%, 31.18%.Keywords: Ipomoea reptans Poir, fasting blood glucose levels, streptozotocin (STZ), metformin.